MODEL RETENSI PADA GENERASI Y : KEEP OR LOOSE THEM? - Ignatius Hari Santoso (Media Riset Bisnis & Manajemen, 2020)
Abstract  PurposeThe purpose of this study is to build a model using the construct of a compensation package, work environment and development opportunities which are assumed to be used to increase retention efforts in Y generation.Design/Metodology/ApproachThis study uses partial least square analysis techniques to test the hypothesis proposed based on a questionnaire that has been filled in by respondents who were selected using purposive sampling method of 100 respondents. Questionnaires are distributed self-administered to workers born in 1980 - 2000 and domiciled in Jakarta, Semarang, Bandung and Surabaya.ResultThis study succeeded in proving that the better the compensation package offered and the more comfortable the work environment is felt, the retention of generation Y will increase.Novelty This study generates a new contradiction that providing opportunities for generation Y workers to develop through training, and opportunities to achieve personal goals are not significant enough to help organizational leaders in increasing retention of generation Y workers. Keywords: Y Generation, Retention, Compensation Package, Working Environment